Corn Performance under Managed Drought Stress and in a Kura Clover Living Mulch Intercropping System. (1st May 2013) - Ziyomo, Cathrine; Albrecht, Kenneth A.; Baker, John M.; Bernardo, Rex
Abstract : A corn ( Zea mays L.) and kura clover ( Trifolium ambiguum M. Bieb.) intercropping system provides ecological services, but competition for water between the grain crop and the living mulch crop often reduces corn yields. Our objectives were to determine (i) if corn that performs well under managed drought (i.e., drought‐tolerant corn) can minimize the grain yield losses incurred when corn is intercropped with kura clover, and (ii) if strong suppression of the kura clover living mulch minimizes the loss in yield of drought‐tolerant and drought‐susceptible corn. From drought trials in Minnesota in 2009 and 2010, we identified five drought‐tolerant and five drought‐susceptible hybrids from the intermated B73 × Mo17 population. Under drought conditions, mean grain yields were 9.66 Mg ha −1 for the drought‐tolerant hybrids and 5.46 Mg ha −1 for the drought‐susceptible hybrids. The 10 hybrids were evaluated in Minnesota and Wisconsin in 2011 in a kura clover intercropping system. Drought‐tolerant hybrids had statistically equal mean yields of 12.90 Mg ha −1 in the killed mulch treatment and 13.69 Mg ha −1 in the living mulch treatment. In contrast, mean yields of drought‐susceptible hybrids were significantly reduced from 4.53 Mg ha −1 in the killed mulch treatment to 3.48 Mg ha −1 in the living mulch treatment. For the drought‐tolerant hybrids, mulch recovery at corn harvest was significantly lower with killed kura clover (41%) than with living kura clover (50%). Our results indicate that the yield of drought‐tolerant corn was not reduced by growing in a living mulch of kura clover.